Feminist Urban Paideias: The Need for New Imaginaries of the Aesthetic Walk - Argüelles Rozada Isabel (Open Cultural Studies)
The contemporary defense of urban strolling finds one of its fundamental legacies in flânerie due to its aesthetic nature and its resistance to utilitarianism. Despite the ethnocentric and androcentric origins of the flâneur, there has been a strong revival of this figure from egalitarian, postcolonial, and gender perspectives, as exemplified by theories on the flâneuse. However, this study argues for the need to abandon this canon due to its limitations in accounting for the specific experiences and needs of female urban strollers. By demonstrating the “aesthetic injustice” of the traditional flânerie approach through various examples of poems, novels, and films from different Western urban contexts, this work proposes a recovery of narratives that have portrayed female urban strollers in alternative ways. These narratives will provide insights into a specifically feminine understanding of urban experience – one shaped by exposure to the male asymmetry of power that governs women’s symbolic access to public spaces, but also by the ability of these characters to momentarily subvert the frameworks of aesthetic injustice through creativity and idleness. Through this analysis, a new horizon of thought will emerge, envisioning alternative forms of urbanity that are authentically sensitive to the feminist perspective.